Pengaruh Edukasi Diet Diabetes Mellitus terhadap Tingkat Pengetahuan Lansia di Posyandu Lansia Desa Karangjati Pandaan Pasuruan - Umi Mardaenatuz Zahro; Faishol Roni; Erna Ts. Fitriyah; Tiara Fatma P; Arif Wijaya (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Background: Diabetes mellitus is a chronic disease that requires long-term management, one of which is through dietary regulation. Older adults as a vulnerable group often experience limited knowledge related to diabetes mellitus diet, which can affect dietary adherence and blood glucose control. Health education is one of the important efforts to improve older adults’ knowledge in managing a diabetes mellitus diet.Objective: This study aimed to determine the effect of diabetes mellitus diet education on the level of knowledge among older adults at the Elderly Posyandu in Karangjati Village, Pandaan District, Pasuruan Regency.Methods: This study employed a pre-experimental research design using a one-group pretest–posttest design without a control group. Sampling was conducted using a total sampling technique. Data processing and analysis were performed using SPSS software version 27.Results: The results showed that before the provision of education, most respondents had a low level of knowledge. After receiving diabetes mellitus diet education, there was an increase in the level of knowledge, with the majority of respondents categorized as having good knowledge. The Wilcoxon test results showed a ρ value = 0.000 (< 0.05), indicating a significant effect of diabetes mellitus diet education on the level of knowledge among older adults.Conclusion: Diabetes mellitus diet education has a positive effect on increasing the level of knowledge among older adults.